Mechano‐based transductive sensing for wearable healthcare - Wang, Ting (2020)
Wearable healthcare presents exciting opportunities for continuous, real-time, and noninvasive monitoring of health status. Even though electrochemical and optical sensing have already made great advances, there is still an urgent demand for alternative signal transformation in terms of miniaturization, wearability, conformability, and stretchability. Mechano-based transductive sensing, referred to the efficient transformation of biosignals into measureable mechanical signals, is claimed to exhibit the aforementioned desirable properties, and ultrasensitivity. In this Concept, a focus on pressure, strain, deflection, and swelling transductive principles based on micro-/nanostructures for wearable healthcare is presented. Special attention is paid to biophysical sensors based on pressure/strain, and biochemical sensors based on microfluidic pressure, microcantilever, and photonic crystals. There are still many challenges to be confronted in terms of sample collection, miniaturization, and wireless data readout. With continuing efforts toward solving those problems, it is anticipated that mechano-based transduction will provide an accessible route for multimode wearable healthcare systems integrated with physical, electrophysiological, and biochemical sensors.